Etyka działania bankowo-ubezpieczeniowego usługodawcy - Czechowska, Iwona (Annales. Etyka w Życiu Gospodarczym, 2009)
The expansion of competition on financial services market forces to search for new ways of development. A bank-insurance cooperation, which is more and more popular in the world and in Poland, becomes an effective remedy to this problem and a factor which stimulates rivalry and competition. The final beneficent of this cooperation is a customer for whom a diverse market offer of financial services means creation of added value. The customer’s satisfaction with that kind of services is important to further development of bank-insurance cooperation. The aim of this work is to estimate whether the services of an integrated bank-insurance offer and insurances with mortgage credits are friendly and useful, and also whether they assure comfort and safety or may cause risk.